Business models for early generation seed production and marketing - Opie, Hellen; Akpo, Essegbemon; Desmae, Haile; Okori, Patrick; Ininda, Jane; Ojiewo, Christopher Ochieng (Wageningen University & Research, 2022)
Sustainable access to early generation seed (EGS) is important for efficient supply of quality certified, standard and/or quality declared seed of improved high-performing crop varieties. Some studies have been conducted from a global perspective on the delivery of EGS with a major focus on the economic analysis and identification of effective pathways for sustainable supply. This study was designed to establish the best practices and critical factors for the delivery of EGS for grain legume and dryland cereal crops in selected countries in sub-Saharan Africa (SSA) and parts of South Asia. A literature review of specific business models applied in SSA and India was conducted. More information was gathered through in-depth interviews with specific key informants drawn from the respective institutions or agencies that were studied. The models include public-sector or research-led models, private -sector models, and public-private partnership models. This working paper presents a synthesis of best practices and approaches through which the specific business models ensure the production and supply of breeder and foundation seeds. The paper identifies practices involving mechanisms for planning, financing, infrastructural facilities required for EGS production, incentives to promote pure line crop EGS production by the private sector, and the methods of production. The study reveals critical constraints for EGS production and supply, including seed market vagaries; the short shelf life of some crop seeds like groundnut; limited maintenance breeding efforts; low quality of breeder seed; lack of infrastructure to produce EGS; breeder seed production does not match the demand for production of foundation seed while foundation seed production does not match the demand for production of certified seed; and high costs of supervising and managing various groups of seed outgrowers. Interventions that build the capacity of seed producers to effectively plan EGS production requirements, guided by a seed roadmap, and product cycle management are needed. The public research institutions need to be strengthened with facilities that enhance their capacity to produce sufficient quantities of breeder seed at the required time. Besides, the proceeds from the sales should “revolve” to enable the unit to make further investments and carry out all the necessary operations in a timely manner. This requires consultation with Governments to set up financial management structures that provide an easier accountability process. Incentive schemes should be developed to encourage investment in the production of pure-line grain legumes and dryland cereals by the private sector as well as enhance their role in popularizing new varieties. Improvement and enforcement of quality assurance and control systems by breeding programmes, including modern technological methods should be considered. Importantly, a handover system that includes lisencing and pre-orders would help to bridge the supply and demand disparity.